Experimental investigation and numerical modeling for induction fans. (15th June 2023) - Wang, Honglei; Wang, Zhichao; Xue, Yu; Li, Xiaomeng; Lu, Yonghong
Abstract: Induced ventilation systems have been widely used in the design of underground space architecture; they are used to agitate the air and eliminate the smoke and harmful gases formed by fire. In the application design of induced ventilation systems, most people often use the Computational Fluid Dynamics (CFD)-technique to simulate and study the flow distribution in underground space buildings. However, there has been little research carried out on the performance of the induction fan, which is a key equipment of induced ventilation systems, especially a lack of experimental verification data on the simulation model of the induction fan. In this paper, the performance of a specific type of axial induction fan is measured experimentally, modeled in CFD. The velocity boundary condition method was adopted for the modeling, and the k-w SST model was adopted for the turbulence model. The CFD model is validated using experimental data on velocity distribution along the axis of the fan jet. The experimental results show that, in addition to wind speed along the jet direction, the axial flow induction fan also has a large deflection wind speed in the y and z directions of 3D space at the outlet. The simulation results show that, along the jet direction, within 1.0 m from the fan outlet, when the efflux induced fan outlet was set to Uniform Wind Speed (UWS), Non-Uniform Wind Speed (NUWS) and Spatial Three-Dimensional Wind Speed (STDWS), the simulation results on average velocity along the jet axis were significantly different from the experimental values. At x  = 1.0 m, the agreement between the STDWS simulation results and experimental values is about 183% higher than that of NUWS. With the development of the jet flow, the simulation results of UWS are basically consistent with those of NUWS, and the simulation results of STDWS are significantly better than those of UWS and NUWS, which are closer to the experimental values. At the far end of the jet, the three simulation values are in good agreement with the actual measured values, and the simulation values of STDWS are closer to the actual measured values. Highlights: The filament method measures the air velocity in three directions ( x, y and z ) at the outlet plane of the induction fan. The simulation study of the jet characteristics uses spatial three-dimensional velocity boundary conditions. The use of spatial three-dimensional velocity boundary conditions can improve the accuracy of simulation results.